Optical Coherence Tomography - Kawasaki, Masanori; Kawasaki, Masanori (IntechOpen, 2013)
Optical coherence tomography (OCT) is an imaging technology that provides high resolution cross-sectional images in many fields of medicine and engineering. OCT images are constructed by measuring the intensity of reflected or back scattered light that is scanned across the tissue and material. This book aims to provide readers with comprehensive information of OCT in ophthalmology, oncology, atherosclerosis and engineering.
English
Keywords: Ophthalmology; Ophthalmology